The transition from the Pre-Pottery to the early Pottery Neolithic period at the site of Uğurlu on the Island of Gökçeada, NE Aegean - Nejat Yücel (Българско е-Списание за Археология)
Uğurlu, on the island of Gökçeada (Türkiye), is among the most important sites in the Aegean when considering the transition from the Pre-Pottery Neolithic to the early Pottery Neolithic. To date, the emergence of pottery in the Aegean has been described based on only a few sites, and except for Uğurlu, transition layers have not been adequately studied. The relatively small Pre-Pottery Neolithic settlement at Uğurlu is about one metre thick and has been divided into seven layers. There is a continuous transition to the pottery layer, around 6600 cal BC. Although pottery production, which emerged without trial and error, indicates pre-existing knowledge, the first pottery was entirely of local production. This paper examines the similarities and differences in material culture between the Pre-Pottery and later Pottery Neolithic layers of Uğurlu.